Vector-borne and other pathogens of potential relevance disseminated by relocated cats - Maggi, Ricardo Guillermo; Halls, Vicky; Krämer, Friederike; Lappin, Michael; Pennisi, Maria Grazia; Peregrine, Andrew S.; Roura, Xavier; Schunack, Bettina; Scorza, Valeria; Tasker, Séverine; Baneth, Gad; Bourdeau, Patrick; et al. (Springer Nature, 2022)
Large populations of unowned cats constitute an animal welfare, ecological, societal and public health issue worldwide. Their relocation and homing are currently carried out in many parts of the world with the intention of relieving suffering and social problems, while contributing to ethical and humane population control in these cat populations. An understanding of an individual cat’s lifestyle and disease status by veterinary team professionals and those working with cat charities can help to prevent severe cat stress and the spread of feline pathogens, especially vector-borne pathogens, which can be overlooked in cats. In this article, we discuss the issue of relocation and homing of unowned cats from a global perspective. We also review zoonotic and non-zoonotic infectious agents of cats and give a list of practical recommendations for veterinary team professionals dealing with homing cats. Finally, we present a consensus statement consolidated at the 15th Symposium of the Companion Vector-Borne Diseases (CVBD) World Forum in 2020, ultimately to help veterinary team professionals understand the problem and the role they have in helping to prevent and manage vector-borne and other pathogens in relocated cats. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Adoption; Animal welfare; Bacteria; Feline; Homing; Importation; Parasites; Prevention; Relocation; Shelter; Viruses; Zoonosis